Compact book rack made from kelempayan (neolamarkia cadamba) and blockboard / Sadam Kahar, Nur Hannani Abdul Latif and Nik Hazlan Nik Hashim - Kahar, Sadam; Abdul Latif, Nur Hannani; Nik Hashim, Nik Hazlan (2014)
Furniture industry in Malaysia has changed over the years. Furniture is very important in our living to fulfil the needs and wants. The objectives of this study are to design a compact book rack made from Kelempayan (Neolamarckia cadamba) and blockboard and to produce a compact book rack that suitable for a limited space and limited budget. The design of this product is multifunction compact book rack which is it can be combine into all-in-one furniture which is can be used as a chair, book rack and table. The results show that the correspondent gave a positive feedback regarding on the material used, multifunction and suitable for limited space and limited budget. Overall, this compact book rack is suitable to commercialize.